Linking evolutionary mode to palaeoclimate change reveals rapid radiations of staphylinoid beetles in low-energy conditions. Issue 4 (22nd October 2019) - Lü, Liang; Cai, Chen-Yang; Zhang, Xi; Newton, Alfred F; Thayer, Margaret K; Zhou, Hong-Zhang
Abstract: Staphylinoidea (Insecta: Coleoptera) is one of the most species-rich groups in animals, but its huge diversity can hardly be explained by the popular hypothesis (co-radiation with angiosperms) that applies to phytophagous beetles. We estimated the evolutionary mode of staphylinoid beetles and investigated the relationship between the evolutionary mode and palaeoclimate change, and thus the factors underlying the current biodiversity pattern of staphylinoid beetles. Our results demonstrate that staphylinoid beetles originated at around the Triassic–Jurassic bound and the current higher level clades underwent rapid evolution (indicated by increased diversification rate and decreased body size disparity) in the Jurassic and in the Cenozoic, both with low-energy climate, and they evolved much slower during the Cretaceous with high-energy climate. Climate factors, especially low O2 and high CO2, promoted the diversification rate and among-clade body size disparification in the Jurassic. In the Cenozoic, however, climate factors had negative associations with diversification rate but little with body size disparification. Our present study does not support the explosion of staphylinoid beetles as a direct outcome of the Cretaceous Terrestrial Revolution (KTR). We suppose that occupying and diversifying in refuge niches associated with litter may elucidate rapid radiations of staphylinoid beetles in low-energy conditions.